Comparison of direct vertebrae rotation and non-direct vertebrae rotation for the correction of adolescent idiopathic scoliosis Lenke 5C: a retrospective study in Changsha, China - Emmanuel Alonge; HongQi Zhang; Shaohua Liu; Yuxiang Wang (Asian Spine Journal)
Study Design A retrospective study. Purpose This study aimed to compare the clinical effectiveness of en-bloc direct vertebrae rotation (DVR) to non-DVR for the correction of Lenke 5C. Overview of Literature The primary goal of posterior correction is to preserve the lumbar spine and achieve a well-balanced spine. However, very few studies have examined the effects of en-bloc DVR (ED) on Lenke 5C correction. Methods A retrospective study was conducted with a minimum follow-up of four years involving 95 patients (ED group, n=45; non-DVR [ND] group, n=50). Radiographic measurements included thoracic kyphosis, lumbar lordosis, sagittal vertical axis, coronal balance, and Cobb angles preoperatively and postoperatively. Flexibility curves and axial vertebral rotation were assessed using computed tomography before and after surgery. Clinical outcomes were evaluated using the Scoliosis Research Society-22 (SRS-22) questionnaire. Results The preoperative major Cobb angles were comparable between the ED group (52.2°±2°) and the ND group (52.8°±3°), with no significant difference (p=0.327). At the last follow-up, the average Cobb angle was significantly lower in the ED group (4.6°±2°) compared to the ND group (6.1°±3°), indicating a significant difference (p=0.005). The postoperative radiographic shoulder height showed no significant difference at the last follow-up. The axial vertebral rotation was significantly greater in the ED group (8.4°±0°) than in the ND group (11.1°±1°) (p=0.001). Additionally, the ED group demonstrated substantial preservation of fusion levels with an average of 5.6 fused segments compared to 6.3 in the ND group. Conclusions A significantly higher incidence of satisfactory outcomes was observed at the final follow-up, with the correction rate of the ED group superior to that of the ND group for adolescent idiopathic scoliosis Lenke 5C. Moreover, patients in the ED group reported better outcomes on the SRS-22 questionnaire and had a shorter hospital stay than those in the ND group.